2012
DOI: 10.1038/ng.2221
|View full text |Cite
|
Sign up to set email alerts
|

Multiple apical plasma membrane constituents are associated with susceptibility to meconium ileus in individuals with cystic fibrosis

Abstract: Variants associated with meconium ileus in cystic fibrosis (CF) were identified in 3,763 patients by GWAS. Five SNPs at two loci near SLC6A14 (min P=1.28×10−12 at rs3788766), chr Xq23-24 and SLC26A9 (min P=9.88×10−9 at rs4077468), chr 1q32.1 accounted for ~5% of the phenotypic variability, and were replicated in an independent patient collection (n=2,372; P=0.001 and 0.0001 respectively). By incorporating that disease-causing mutations in CFTR alter electrolyte and fluid flux across epithelia into an hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
248
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(258 citation statements)
references
References 37 publications
6
248
1
3
Order By: Relevance
“…Adjunctive functional in vivo tests, i.e., nasal potential difference measurements and the novel β-adrenergic sweat secretion assay, 24 confirmed that the variant c.3700 A>G led to reduced CFTR channel function on the apical membrane of these CF-affected tissues. This clinical phenotype is incompatible with the prediction that this variant caused the missense mutation, p.Ile1234Val.…”
Section: Discussionmentioning
confidence: 79%
“…Adjunctive functional in vivo tests, i.e., nasal potential difference measurements and the novel β-adrenergic sweat secretion assay, 24 confirmed that the variant c.3700 A>G led to reduced CFTR channel function on the apical membrane of these CF-affected tissues. This clinical phenotype is incompatible with the prediction that this variant caused the missense mutation, p.Ile1234Val.…”
Section: Discussionmentioning
confidence: 79%
“…These results suggest SLC26A9 as a modifier and novel therapeutic target in CF and potentially other mucostatic airway diseases, including severe asthma and COPD. Of note, SLC26A9 was also found to contribute to the risk of meconium ileus in CF in a recent genome-wide association study [114]. The high throughput screens of large chemical libraries, developed to identify compounds that rescue mutant CFTR [59,61], are now available for the discovery of drugs that open TMEM16A and SLC26A9 Cl -channels directly without altering cytosolic Ca…”
Section: Slc26a9-mediated CLmentioning
confidence: 99%
“…6 Further, MI demonstrates notable heritability. 7,8 Although studies have shown that non-CFTR genes contribute to susceptibility, 9 the CFTR genotype itself affects the occurrence of this complication; only patients with the more severe CFTR variants are at risk for MI.…”
Section: Introductionmentioning
confidence: 99%